2013
DOI: 10.1007/s13277-013-1223-z
|View full text |Cite
|
Sign up to set email alerts
|

Oxymatrine induces mitochondria dependent apoptosis in human osteosarcoma MNNG/HOS cells through inhibition of PI3K/Akt pathway

Abstract: The cytostatic drug from traditional Chinese medicinal herb has acted as a chemotherapeutic agent used in treatment of a wide variety of cancers. Oxymatrine, classified as a quinolizidine alkaloid, is a phytochemical product derived from Sophora flavescens, and has been reported to possess anticancer activities. However, the cancer growth inhibitory effects and molecular mechanisms in human osteosarcoma MNNG/HOS cell have not been well studied. In the present study, the cytotoxic effects of oxymatrine on MNNG/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 37 publications
2
37
0
Order By: Relevance
“…ERK/mitogen-activated protein kinase (MAPK) and PI3K/ Akt pathway are often aberrantly activated in human cancers and contribute to cell proliferation and metastasis [17,22,23]. As a result, Western blot analysis showed that MALAT1 c Western blots analysis of the ERK/MAPK and PI3K/Akt pathway-related proteins in the U-2 OS cells.…”
Section: Suppression Of Pi3k/akt Pathways By Malat1 Knockdownmentioning
confidence: 99%
“…ERK/mitogen-activated protein kinase (MAPK) and PI3K/ Akt pathway are often aberrantly activated in human cancers and contribute to cell proliferation and metastasis [17,22,23]. As a result, Western blot analysis showed that MALAT1 c Western blots analysis of the ERK/MAPK and PI3K/Akt pathway-related proteins in the U-2 OS cells.…”
Section: Suppression Of Pi3k/akt Pathways By Malat1 Knockdownmentioning
confidence: 99%
“…Studies have proved that inhibition of Akt is involved in apoptosis (Zhang et al, 2013;Won et al, 2014). To identify whether Akt is involved in SW-induced apoptosis through overexpression of Fyn, we examined Akt and its phosphorylation at residue 473.…”
Section: Overexpression Of Fyn Elevated Phosphorylation Of Akt and P-mentioning
confidence: 99%
“…In human osteosarcoma MNNG/HOS cell line, oxymatrine induces mitochondria dependent apoptosis by inhibiting the PI3K/Akt pathway (15). In an in intro and in vivo experiment, oxymatrine shows an antiangiogenic effect on pancreatic cancer through inhibition of the NF-κB-mediated VEGF signaling pathway (16).…”
Section: Diterpenoidmentioning
confidence: 99%